Memorial acadêmico: trajetória escolar, acadêmica e profissional - CARDOSO, Elcilene da Silva (2022)
In this End of Course Work (TCC), written as an Academic Memorial, I had as a general objective to report my school, academic and professional life. It includes my trajectory and the situations I went through before and during the course of Licentiate in Pedagogy at the Federal University of Pará, University Campus of Altamira. It also shows how the educational process happens in the life of a woman who decides to study and reach higher education in Brazil, thus providing a better view of the reality experienced by us women in the search for knowledge and a better life. This study is qualitative in nature. In it I also establish relationships between the most important phases of my life, from my early school years until now.